Greenwashing dalam Pelaporan Keberlanjutan: Konstruksi Makna dan Dilema Profesional Akuntan Manajemen pada Perusahaan Manufaktur Terbuka di Indonesia - Ratih Dewi Titisari Haryana; Herlambang Pudjo Santosa; Nur Hidayah (LPPM STIE YAPAN, 2025)
The practice of greenwashing, misleading environmental sustainability claims without real substance has become a serious threat to the integrity of sustainability reporting in Indonesia after the implementation of POJK Number 51/POJK.03/2017. This research aims to explore how management accountants and internal auditors in public manufacturing companies construct meaning, respond and negotiate pressure to legitimize environmental claims of dubious truth. The research uses a qualitative approach with an interpretive phenomenological design. Data was collected through semi-structured in-depth interviews with 18 informants consisting of senior management accountants, sustainability managers, internal auditors, and audit committees from six manufacturing companies listed on the Indonesia Stock Exchange. The analysis technique uses interpretative phenomenological analysis (IPA). The results of the study reveal three main themes: (1) the dual institutional pressures that drive decoupling between narratives and environmental realities; (2) the moral rationalization that accountants use to negotiate their professional integrity; and (3) the limited verification capacity of internal auditors in detecting environmental claims non-conformity. This research contributes to the environmental accounting literature by presenting the perspectives of internal actors that have rarely been studied, and offers policy implications for regulators, the accounting profession, and the board of commissioners in strengthening the integrity sustainability reporting ecosystem.